Automatické monitorování hustoty kapaliny - Bebej, Rastislav (Vysoké učení technické v Brně. Fakulta strojního inženýrství, 2022)
Táto práca sa zameriava na vytvorenie zariadenia schopného monitorovať hustotu kvapalín pri fermentačnom procese. Súčasťou práce je výber vhodného princípu merania hustoty kvapalín, doplneného kompenzáciou vplyvu teploty, výber vhodných súčiastok a návrh schémy ich zapojenia. Ďalej sa práca zaoberá návrhom dosky plošného spoja a bezdrôtovým odosielaním dát do počítača s použitím Wi-Fi.

This thesis focuses on creating a device capable of monitoring the density of liquids during the fermentation process. The thesis includes the selection of a suitable principle for the measurement of the density of liquids, including the temperature compensation, the selection of suitable components and the design of schematics. Furthermore, the thesis deals with the design of a printed circuit board and wireless data transmission to a computer via Wi-Fi.
Automatic monitoring of fluid density
Keywords: Hustota kvapalín; akcelerometer; mikrokontrolér; AD prevodník; Wi-Fi; Density of fluids; accelerometer; microcontroller; AD converter; Wi-Fi